L’expérience collective des archives - Delphine Frasch (Glad!)
This article offers an introduction to the English feminist history of the 70s, little known in France, and it analyzes the activist contexts in which this history emerged. The paper shows how this history critically reappropriates a socialist history « from below » which was represented, at the end of the 60s, by E.P. Thompson and the History Workshop movement around Raphael Samuel. The core of the history from below has been the project of inventing an experience of the archives, through which to create a connexion both intimate and collective to the experiences of ordinary people and women of the past. This approach aims to promote the development of radically democratised forms of knowledge-production and circulation, and thus, the sustenance of socialist and feminist mobilizing « from below ».